New data on the structure and motion of the ice sheet in the area of a runway of the Novolazarevskaya Reserch Station (East Antarctica) - A. Boronina S.; M. Kashkevich P.; S. Popov V.; E. Mikhailov M.; A. Druzhin E.; А. Боронина С.; М. Кашкевич П.; С. Попов В.; Е. Михайлов М.; А. Дружин Е. (IGRAS, 2024)
Currently, the Russian Federation has the only “blue ice” runway in Antarctica. It is located on the Queen Maud Land and is a part part of the landing site of the Russian Novolazarevskaya Station. This is one of the largest aviation transport hubs in the Indo-Atlantic sector of the continent, capable of landing heavy aircraft with wheeled chassis. Despite all the advantages that “blue ice” runways have, due to their location on the glacier, they are subject to dangerous glaciological processes caused by the ice sheet motions. The purpose of this research is to study the structure of the ice sheet along the runway and in the vicinity of the airbase Novo Runway (Novolazarevskaya Station), as well as to continue monitoring the uneven flow of the glacier, which began in 2021. The article presents the results of field studies carried out from December 2023 to February 2024, which included georadar profiling at a frequency of 150 MHz and three definitions of the coordinates of the runway markings to estimate their displacement for the summer season of 2023/24.There are also presented: a comparison of the values of the ice sheet deformation within the runway limits measured in the autumn of 2021 and the Antarctic summer of 2023/24, the calculation of deformations for the two-year period of monitoring, and the analysis of air temperature data for 2014–2024 from the weather station of the Novo Runway. It was found that at the beginning of the runway (up to 800 m) small healed crevasses are observed. This area requires regular visual monitoring. The central part of the runway appears to be the most complex in structure, demonstrating relatively high deformations in the marginal parts and characterized by large vertical structures in the glacier. In the long term, this area, as well as about 400 m at the end of the runway, are the most unstable. A joint analysis of data on the displacement of runway markings for 2021 and 2023/24 showed that values of the deformations may differ by an order of magnitude from year to year. ...